Analisis Faktor-faktor Yang Mempengaruhi Kualitas Laporan Keuangan Usaha, Kecil, Mikro dan Menengah (UMKM) di Pasar Beringharjo - Anggriyani, Tassya; Nugraeni, Nugraeni (Politeknik Negeri Ambon, 2024)
MSMEs after the economic crisis continued to increase from year to year, this proves that MSMEs are able to survive in the midst of the economic crisis. MSMEs have been proven to absorb a larger workforce in the national economy. The impact that causes the decline in the quality of financial reports is due to the lack of understanding of accounting in the preparation of financial reports, This research approach uses qualitative research which aims to provide an understanding of recording financial reports and analyzing existing problems. With an accounting background, it will be easier to understand accounting because they already have an understanding of accounting. From the results of the interviews above, according to the researcher MSMEs are not interested in participating in the socialization of financial report recording. This is one of the lack of awareness for recording training because they have different levels of understanding of accounting, so that financial recording has variations in recording. In order to increase awareness and understanding of accounting, it is necessary to conduct active socialization and training for MSMEs according to what is needed. Recording can be done in a simple but effective way for MSMEs which can help actors.